Analisis Kesalahan Siswa Tipe Kepribadian Thinking dan Feeling dalam Menyelesaikan Soal HOTS berdasarkan Newman’s Error Analysis - Murtafiah, Inni; Susanto; Suwito, Abi (Griya Journal of Mathematics Education and Application, 2024)
This research is a descriptive study which aims to describe the errors made by students in solving HOTS mathematics problems based on Newman's error analysis. This research was conducted at MTs NU Al Badar with research subjects of 1 student with a thinking personality type and 1 student with a feeling personality type. The research instrument used in this research is a test instrument in the form of HOTS type mathematics questions with material on Building a Curved Side Room with 3 questions and an interview guide. The results of the research obtained information that the errors made by students when working on high order thinking skills (HOTS) type mathematics problems with the material Building Curved Side Spaces were divided into four types of error categories, namely errors in understanding the problem (comprehension errors), transformation errors (transformation errors). errors), processing skills errors, and errors in writing answers (encoding errors).